Developing Authentic Assessment Instrument on Short Story Appreciation and Production for Senior High School Students - Purwadi Susilo; Ratu Wardarita (JETL (Journal of Education, Teaching and Learning), 2017)
This study was conducted as the follow-up action toward the result of a preliminary study which showed that Indonesian Language teachers in Senior High School (mentioned as “SMA”) YPI Tunas Bangsa Palembang had not yet implemented any standardized, objective, accurate nor appropriate assessment instruments as demanded by the 2013 curriculum. Based on this problem, the research question in this study was “How are teachers’ necessities of an authentic assessment instrument to assess understanding on the short stories production and appreciation in SMA YPI Tunas Bangsa Palembang?”. This study employed the research and development method adapted from the one proposed by Akker which consisted of several steps: (1) analysis, (2) design, (3) evaluation, and the one by Tessmer: (1) self-evaluation, (2) expert judgment, (3) one-to-one, (4) small group, (5) revision, and (6) field test. The implementation of the authentic assessment for short stories production and appreciation was analyzed by using the inter-rater agreement. The inter-rater reliability was measured using the Cronbach’s Alfa. The data were also analyzed using the SPSS 16 program which resulted to a level of significance at 0.5. Therefore, it is found that the evaluation given by the experts and the respondents reached a similar perception. Based on the result of the Cronbach’s Alpha test, a value of 0.99 was obtained above 0.70 which implies that the authentic assessment instruments developed in this study are highly reliable.